The purpose of radio and how it supports older adults' wellbeing - Krause, Amanda E.; Fletcher, Heather (Frontiers in Computer Science, 2023)
In Australia today, radio continues to draw large audiences, with high engagement among older adults. This research investigated how radio personnel and listeners regard the purpose of radio, and further how engaging with radio is perceived to influence listener well-being. Thematic analysis of semi-structured interviews with radio personnel (N = 16) and focus groups with older adult listeners (N = 32) suggest that the purpose of radio is to stay informed (e.g., news and information), for entertainment (e.g., music), and for perceived social purposes (e.g., communion, social connection, company, and companionship). Findings indicate there are implicit and explicit ways in which radio facilitates the well-being of their listenership. Explicitly, radio promotes mental health through broadcasts and programming, as well as exploiting the medium of radio as a public service for the community to call and rely on. Participants implicitly indicated that radio acts as a surrogate friend in their home; someone to keep them company and encourage connection to their greater community. Broadly, perceived relationships with radio programs and individual presenters, built and sustained over time through repeating listening, underpin the radio’s ability to support listener well-being. These findings have implications for broadcasting practices as well as future work concerning how the radio might be used as a widely accessible tool for promoting quality of older life.